1998
DOI: 10.1002/(sici)1521-4109(199806)10:7<458::aid-elan458>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The Catalysis of the Reduction of BiIII Ions by Methionine

Abstract: A multistep reduction of Bi III ions at the dropping mercury electrode in 1M HClO 4 with the addition of methionine was examined using an impedance method in wide potential and frequency ranges. It was found that the standard rate constants and the rate constants of the first electron transfer increase with the concentration increase of methionine. The rectilinear relation k f ¼ f(G) indicates formation of Bi-methionine bridges which facilitate the transfer of electrons across the inner layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The values of the apparent rate constants k f were obtained with the precision of AE 5% from the charge-transfer resistance [33]. The details are described elsewhere [34,35].…”
Section: Impedance Measurementsmentioning
confidence: 99%
“…The values of the apparent rate constants k f were obtained with the precision of AE 5% from the charge-transfer resistance [33]. The details are described elsewhere [34,35].…”
Section: Impedance Measurementsmentioning
confidence: 99%
“…Studies on the kinetics of various depolarisers in the presence of electrode substances are comprehensively discussed in the literature [5][6][7][8][9][10][11]. It was demonstrated that the structures of the inter-phase area caused by adsorption of organic compounds on the surface of mercury play a significant role in the mechanism of the cap-pair effect.…”
Section: Introductionmentioning
confidence: 99%
“…The studies concerning the catalytic activity of many different organic substances on the electroreduction of: Zn(II) [1,[3][4][5][6], In(III) [2,7,8], Eu(III) [9] Cd(II) [10] and Bi(III) [11] ions demonstrated that the electroreduction mechanism of these depolarizers in the presence of organic substances is complex, containing both the electron transfer stages and the chemical stages, in which a substrate or intermediate compound lose the part of solvation shell forming at the electrode surface the complexes participating in electrons transfer. In the mechanisms of these processes the water molecules were also taking into consideration, because the behaviour of water at the electrode-solution interface is of a fundamental interest in electrochemistry as water is an essential component of electrochemical systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was said [11] that methionine (Mt) accelerates the electroreduction process of Bi(III) ions in 1 mol dm À3 HClO 4 . It was found that the standard rate constants and the constants of the first electron transfer increase with the increase of methionine concentration.…”
Section: Introductionmentioning
confidence: 99%